THE ROLE OF SELF AWARENESS IN MEDIATING THE INFLUENCE OF USMANI METHODS AND LEARNING INTENSITY ON THE ABILITY TO READ THE QUR'AN MAHASANTRI MA'HAD AL-JAMI'AH IAIN PONOROGO - Muazamsyah, Yusuf Annas; Daryono, Rihab Wit; Ghafar, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research investigates the role of self-awareness in mediating the impact of the Usmani method and learning intensity on Al-Qur'an reading proficiency among Ma'had Al-Jami'ah IAIN Ponorogo students. Using a quantitative survey method, data were collected from 61 mahasantri through a Likert scale questionnaire and analyzed with descriptive statistics and regression analysis. Findings revealed that while the Usmani method positively influenced self-awareness (0.419; 0.001), self-awareness itself did not significantly affect Al-Qur'an reading ability (0.512; 0.057). Additionally, self-awareness did not mediate the effects of the Usmani method (0.215; 0.101) and learning intensity (0.288; 0.090) on Al-Qur'an reading proficiency. These results underscore the limited mediating role of self-awareness. Consequently, it is recommended that Ma'had Al-Jami'ah IAIN Ponorogo incorporate self-awareness development programs into the Al-Qur'an curriculum through workshops and reflection sessions. The Usmani method should be tailored to individual needs, and learning intensity should be optimized to ensure effective and efficient use of students' time and energy.